Psychosis in parkinsonism: an unorthodox approach - Onofrj M (Dove Medical Press, 2017)
Marco Onofrj,1,2 Danilo Carrozzino,3,4 Aurelio D’Amico,1,2 Roberta Di Giacomo,1,2 Stefano Delli Pizzi,1 Astrid Thomas,1,2 Valeria Onofrj,5 John-Paul Taylor,6 Laura Bonanni1,2 1Department of Neuroscience Imaging and Clinical Sciences, University “G. d’Annunzio” of Chieti-Pescara, 2CE.S.I. University Foundation, 3Department of Psychological, Health, and Territorial Sciences, University “G. d’Annunzio” of Chieti-Pescara, Chieti, Italy; 4Psychiatric Research Unit, Psychiatric Centre North Zealand, Copenhagen University Hospital, Hillerød, Denmark; 5Department of Bioimaging, University Cattolica del Sacro Cuore, Rome, Italy; 6Institute of Neuroscience, Campus for Ageing and Vitality Newcastle University Newcastle upon Tyne, Newcastle upon Tyne, UK Abstract: Psychosis in Parkinson’s disease (PD) is currently considered as the occurrence of hallucinations and delusions. The historical meaning of the term psychosis was, however, broader, encompassing a disorganization of both consciousness and personality, including behavior abnormalities, such as impulsive overactivity and catatonia, in complete definitions by the International Classification of Diseases-10 (ICD-10) and the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). Our review is aimed at reminding that complex psychotic symptoms, including impulsive overactivity and somatoform disorders (the last being a recent controversial entity in PD), were carefully described in postencephalitic parkinsonism (PEP), many decades before dopaminergic treatment era, and are now described in other parkinsonisms than PD. Eminent neuropsychiatrists of the past century speculated that studying psychosis in PEP might highlight its mechanisms in other conditions. Yet, functional assessments were unavailable at the time. Therefore, the second part of our article reviews the studies of neural correlates of psychosis in parkinsonisms, by taking into account both theories on the narrative functions of the default mode network (DMN) and hypotheses on DMN modulation. Keywords: postencephalitic parkinsonism, Parkinson’s disease, psychosis, default mode network, atypical parkinsonism